1999
DOI: 10.1023/a:1006331707605
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In maize, a layer of basal endosperm cells adjacent to the pedicel is modified for a function in solute transfer. Three genes specifically expressed in this region, termed the basal endosperm transfer layer (BETL-2 to -4), were isolated by differential hybridization. BETL-2 to -4 are coordinately expressed in early and mid-term endosperm development, but are absent at later stages. BETL-2 to -4 coding sequences all predict small (< 100 amino acids), secreted, cysteine-rich polypeptides which lack close relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…That being the case, BETL9 would add to the number of proteins expressed at the BETL with presumed or already proven anti pathogenic activity. BETL1 , BETL3, and meg-1 (Hueros et al, 1995, 1999; Gutiérrez-Marcos et al, 2004) genes code for proteins related to the antimicrobial peptides defensins. BETL4 has some similarity to alpha-amylase/trypsin inhibitors (Thompson et al, 2001) and BETL2 was renamed as BAP-2 (basal layer antifungal protein 2) after been demonstrated that it has antifungal activity in vitro (Serna et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That being the case, BETL9 would add to the number of proteins expressed at the BETL with presumed or already proven anti pathogenic activity. BETL1 , BETL3, and meg-1 (Hueros et al, 1995, 1999; Gutiérrez-Marcos et al, 2004) genes code for proteins related to the antimicrobial peptides defensins. BETL4 has some similarity to alpha-amylase/trypsin inhibitors (Thompson et al, 2001) and BETL2 was renamed as BAP-2 (basal layer antifungal protein 2) after been demonstrated that it has antifungal activity in vitro (Serna et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In maize there is already an extensive collection that includes genes named as BETL1 , 2 , 3, and 4 (Hueros et al, 1995, 1999) encoding for small cysteine-rich proteins. The product of the BETL2 gene was renamed BAP-2 (basal layer antifungal protein 2) after its in vitro antifungal activity was demonstrated (Serna et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about the molecular signals that induce TC differentiation, some genes expressed associated with TCs have been described (Hueros et al, 1995, 1999; Gómez et al, 2002; Gutiérrez-Marcos et al, 2004; Muñiz et al, 2006). Among these the Myb-related protein-1 ( MRP-1 ) was the first TC-specific transcriptional activator identified in plants (Gómez et al, 2002) and was shown to be a key regulator of TCs differentiation process in maize endosperm (Gómez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, sugars and the hormones abscisic acid (ABA) and cytokinin have been shown to reach the mother-seed interface in high concentrations and affect the kernel development significantly [17-19], suggesting that transfer cells possibly play a role in the interpretation and further transmission of those signals. In recent years a number of transfer cell specific genes have been described [20-22] including a MYB-related transcription factor, ZmMRP-1 , which controls the expression of several of these genes [23] through interaction with specific DNA motifs in their promoters [24]. In a previous paper we reported the isolation of ZmTCRR-1 , a type-A response regulator exclusively expressed in the transfer cell layer of the maize caryopsis during early development, and transcriptionally controlled by ZmMRP-1 .…”
Section: Introductionmentioning
confidence: 99%